2016
DOI: 10.1016/j.ijrobp.2016.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Phase 2 Study of Concurrent Chemoradiation Therapy (CCRT) Versus Chemotherapy Alone in Stage IV Esophageal Squamous Cell Carcinoma (ESCC)

Abstract: Purpose/Objective(s): Stage IV ESCC carries a poor prognosis with a median survival of 6-9 months. The standard treatment has traditionally been chemotherapy. Palliative radiation therapy was used for symptom relief. The optimal treatment for stage IV ESCC has not yet been established. The aim of this study was to compare the efficacy and safety of CCRT versus chemotherapy alone in patients with stage IV ESCC. Materials/Methods: Patients with stage IV ESCC were randomly assigned to the CCRT group and the chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…In a large cohort of 12,683 patients with metastatic EC, Guttmann et al ( 13 ) reported that definitive-dose (≥50.4 Gy) CRT was associated with superior survival compared to CT alone (median OS 8.3 vs. 11.3 months). As shown in Table 2 , the clinical survival outcomes of the metastatic population in this study were highly consistent with those of previous studies ( 13 , 18 21 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In a large cohort of 12,683 patients with metastatic EC, Guttmann et al ( 13 ) reported that definitive-dose (≥50.4 Gy) CRT was associated with superior survival compared to CT alone (median OS 8.3 vs. 11.3 months). As shown in Table 2 , the clinical survival outcomes of the metastatic population in this study were highly consistent with those of previous studies ( 13 , 18 21 ).…”
Section: Discussionsupporting
confidence: 90%
“…In terms of metastatic EC, extended survival after definitive CRT has been reported by several previous studies. A prospective randomized phase 2 study demonstrated that the CRT was associated with significantly improved median PFS (9.3 vs. 4.7 months, p = 0.021) and median OS (18.3 vs. 10.2 months, p = 0.001) than CT alone ( 18 ). Moreno et al ( 19 ) also suggested that additional RT could derive better survival compared to CT alone with extended 2- and 5-year OS of 6.4% and 2.7%, respectively (p <.001).…”
Section: Discussionmentioning
confidence: 99%
“…The survival benefit of definitive-dose radiotherapy in stage IV esophageal cancer has been suggested by several previous studies evaluating concurrent chemoradiotherapy when compared with chemotherapy alone. 30 , 46 , 47 , 48 Our study extends these findings, using a more contemporary patient population with multivariable models that adjust for metastatic pattern at presentation (nodal only, single organ, multiorgan) and exclude patients in the control arm that were felt not to be healthy enough to be irradiated.…”
Section: Discussionmentioning
confidence: 53%
“…( 13 ) found that combining surgery with radiotherapy could improve survival in metastatic EC, it based on older populations, older methods of radiotherapy, and did not analyze the clinical benefits of chemotherapy combined with radiation therapy. A phase II study compared concurrent chemoradiation therapy (CCRT) with chemotherapy alone in stage IV esophageal squamous cell carcinoma, demonstrating that CCRT significantly prolonged median progression-free survival (mPFS, 9.3 vs. 4.7 months, P=0.021) and mOS (18.3 vs. 10.2 months, P=0.001) ( 14 ). This study challenged the status of standard treatment modality for metastatic EC treated with chemotherapy alone.…”
Section: Discussionmentioning
confidence: 99%